ANALISIS PENERAPAN METODE AL-BAGHDADI DALAM MENINGKATKAN KEMAMPUAN BACA TULIS AL-QUR’AN (BTA) - Amaliah, Fitrah; Cindrya, Elsa; Febrieanitha Putri, Yecha; Marlina, Leny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of the Al-Baghdadi method in improving Qur’anic reading and writing skills (BTA) among students at TPA Al-Fitrah in Kenten Jaya Village, Banyuasin. This research employed a qualitative approach using observation and interviews as data collection techniques involving the TPA management, teachers (ustadzah), and students. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results show that the implementation of the Al-Baghdadi method is carried out gradually through the introduction of hijaiyah letters and their articulation points (makhraj), providing reading examples by the teacher, imitation activities conducted collectively and individually, as well as practice in reading syllables and short verses. The application of this method was found to help improve students’ Qur’anic reading skills in a more structured manner. The study also identified several challenges in the learning process, including differences in students’ abilities, limited learning media, and unstable learning concentration among children. To address these challenges, teachers applied several strategies such as individualized guidance, variations in teaching methods, and providing motivation to students. Therefore, the Al-Baghdadi method can serve as an effective learning method to enhance Qur’anic reading and writing skills when implemented consistently and supported by appropriate instructional strategies aligned with students’ characteristics.